2009
DOI: 10.1210/jc.2008-1851
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with a Low Glomerular Filtration Rate in Primary Aldosteronism

Abstract: In a large cohort of patients with PA, markers of disease activity such as plasma aldosterone and serum potassium are independent predictors of a lower GFR. Specific interventions, such as adrenalectomy or spironolactone treatment, are associated with a further decline in GFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
3
6

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 19 publications
8
160
3
6
Order By: Relevance
“…The German Conn's Registry (www.conn-register.de) is a multi-center database analyzing comorbidities and long-term outcome of patients with PA (2,3,21). Since the initiation of the prospective phase in October 2008, all patients actively treated within the centers were entered in a common database after pseudonymization (22).…”
Section: Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The German Conn's Registry (www.conn-register.de) is a multi-center database analyzing comorbidities and long-term outcome of patients with PA (2,3,21). Since the initiation of the prospective phase in October 2008, all patients actively treated within the centers were entered in a common database after pseudonymization (22).…”
Section: Design and Patientsmentioning
confidence: 99%
“…Primary aldosteronism (PA) is the most common form of secondary hypertension and affects up to 10% of all hypertensive patients (1,2,3,4,5). Patients with PA have an increased risk of developing relevant comortalities and comorbidities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…50 Five other studies, with spironolactone uptitrated as needed and tolerated, revealed effects no different from those of surgery. [44][45][46]48,53,55 PA patients treated with spironolactone or amiloride experience an improvement in wellbeing similar to that observed after adrenalectomy, although these effects appear to be established more slowly. 86 …”
Section: Outcomes Of Drug-based Treatmentmentioning
confidence: 78%
“…40 They are most marked in patients with unilateral PA 41,42 and are reversed within one month of adrenalectomy (Figure 1). 40,[43][44][45][46][47][48][49][50][51][52][53][54][55] Hemodynamic stress and hyperaldosteronism per se lead to chronic structural damage in the long run. 45,56 PA patients have been reported to display a certain level of insulin resistance, which may improve after adrenalectomy.…”
Section: Outcomes Of Adrenalectomy In Unilateral Pamentioning
confidence: 99%
See 1 more Smart Citation